PELATIHAN DASAR INTERNET OF THINGS (IOT) SEBAGAI USAHA PENINGKATAN KOMPETENSI TEKNOLOGI BAGI SISWA PESANTREN DARUSSALAM - Putri Madona; Jajang Jaenudin; Tianur (Politeknik Caltex Riau, 2025)
The rapid development of technology, especially the Internet of Things (IoT), has brought major changes in various aspects of life, including Islamic-based education in Islamic boarding schools. IoT, which was originally used for smart household devices, has now expanded to various sectors such as industry, health, transportation and agriculture, which has a significant impact on efficiency and quality of life. Even though the Darussalam Islamic Boarding School focuses on comprehensive religious education, it has the potential to adapt to technological developments through the facilities available, such as a computer laboratory with internet access. Politeknik Caltex Riau took the initiative to organize basic IoT training as a form of community service, with the aim of increasing technological competence for students. Apart from that, this activity is also a promotional medium for the Politeknik Caltex Riau in supporting Islamic education and empowering the community through mastery of the latest technology. The evaluation results of the activity, conducted through questionnaire responses, indicate an increase in the students' knowledge regarding both the theory and simple implementation of IoT as reflected in the questionnaire outcomes.